Quality criteria for conceptual technology integration models in education: bridging research and practice - Tondeur, Jo; Petko, Dominik; Christensen, Rhonda; Drossel, Kerstin; Starkey, Louise; Knezek, Gerald; Schmidt-Crawford, Denise A. (Educational technology research and development, 2021)
In order to effectively use technology in education, appropriate conceptual understandings are needed to guide the integration process. Today, there is a wide range of conceptual models that are developed and used in research and/or practice focusing on educational technology integration. Conceptual models are of relevance as they can bridge theory with practical applications. Today, there are a wide range of conceptual models are developed and used in research and/or practice focusing on educational technology integration. These models can be seen as simplified versions of theories for practical application or as condensed wisdoms of practice that need to be further investigated theoretically and empirically. However, there is insufficient agreement on the dimensions and criteria used to judge the quality of conceptual models in educational technology. Therefore, the main goals of this article are to: (1) develop criteria to assess the quality and scope of conceptual models and (2) identify and compare exemplary models for technology integration in educational settings along with these quality criteria. The resulting five criteria from this investigation provide the means to effectively evaluate the quality and scope of conceptual models focused on technology integration while providing additional insight into applying these models in research and practice.